Perancangan Keamanan Pengguna Cardless dari Ancaman Cyber Crime Menggunakan Kriptografi Curva Elliptic - Nevy Bella Samantha; Senie Destya; Wahid Miftahul Ashari (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
In this era, technology has discovered new innovations by creating practical ways of making transactions. Cash withdrawal transactions are now much easier because a new way has been discovered, where people can make transactions without using a card. This is certainly very useful for people whose wallets are often left behind. This ease of carrying out transactions is called Cardless. Cardless itself is a cardless cash withdrawal service that offers a fast and time-saving transaction process. Apart from that, cardless cards also have several advantages, including ATM cards being safer from the risk of being swallowed or left behind by the ATM, and avoiding the risk of fraud. Like technology in general created by humans, cardless certainly also has disadvantages. This transaction has the potential for identity theft, uncontrolled spending, system compromise, and not everyone uses cardless cash withdrawal transactions due to lack of socialization of the use of cardless transactions. In this research, the researcher wants to recommend designing additional security in the m-banking application. Different from previous research, this time the researcher used the Elliptic Curve method. The subjects of this research are cardless users. The goal to be achieved in this research is that the security of the m-banking application when using cardless transactions becomes safer because the calculation of the algorithm has been added to randomize or encrypt the PIN. The function of encrypting the PIN itself is aimed at making it more difficult for criminals to successfully carry out crimes. . If the level of security is not added as recommended by the author, the bank will have to think of other ways to increase security when carrying out cardless transactions because then more customers or users will become victims. From the encryption results in this research, the PIN was previously 312143, after the encryption process was carried out, the PIN changed to DUDSDTDSDVDU. Of course, in the future technology will continue to develop and perhaps even bigger flaws will be created, but up to now Elliptic Curve cryptography is still cryptography that is difficult to solve. With so little chance that cybercrime perpetrators can break in.